Weak taxation and constraints of the welfare state in democratized Taiwan. (29th August 2018) - Lin, Chenwei
Abstract: The relationship between taxation and welfare regime in Taiwan has largely been unexplored to date. This study argues that since taxation capacity of the state decides the fate of new welfare programs such as the public provision of long-term care, it also affects the trajectory of the welfare regime. Through the analysis of Taiwan's tax revenue structure and tax base, this study reveals that Taiwan, unlike many new democracies, has shone away from relying on goods and services taxes but at the same time continues to provide preferential tax treatment for the corporate world. The result has been the erosion of tax base which makes introducing new welfare programs extremely difficult even when new policies allow for credit-claiming. Therefore, the familialistic welfare regime persists because of a weakened taxation capacity. Furthermore, the political determinants of the weakened taxation capacity can be found in identity-based party politics, an influential capital vs acquiescent labor and the limited bargaining power of civil society.